Allomedmassa, a new spider genus from evergreen forests of Southeast Asia (Araneae: Corinnidae) - Dankittipakul P. (Museum d'Histoire Naturelle de Geneve, 2014)
Allomedmassa gen. nov. is established for three relatively large, non ant-mimicking species of the subfamily Castianeirinae from evergreen forests of Thailand and Borneo. The new genus can be distinguished from other Asian Castianeirinae genera by the strongly convex dorsal surface of its carapace, by the sigmoid sperm duct of the palpal organ, by the strongly sclerotized embolus, and by the elaborate retrolateral tibial apophysis of the palp. Female copulatory orifices are greatly enlarged, leading to elongated spermathecae. On the basis of morphological similarities, Allomedmassa gen. nov. appears closely related to Medmassa Simon, 1887. Three species are described: A. mae sp. nov., A. day sp. nov., and A. deelemanae sp. nov.